25.3k views
5 votes
Please help me with this question.​

Please help me with this question.​-example-1
User Compholio
by
6.1k points

1 Answer

3 votes

Answer:


\purple{ \boxed{(d^(2) y)/(dx ^(2) ) = \frac{132}{ {x}^(13) } }}

Explanation:


y = \frac{1}{ {x}^(11) } \\ y = {x}^( - 11) \\ (dy)/(dx) = (d)/(dx) {x}^( - 11) \\ (dy)/(dx) = - 11{x}^( - 11 - 1) \\ (dy)/(dx) = - 11{x}^( - 12) \\ \\ (d)/(dx) \bigg((dy)/(dx) \bigg) = (d)/(dx) ( - 11 {x}^( - 12) ) \\ \\ (d^(2) y)/(dx ^(2) ) = - 11(d)/(dx) ( {x}^( - 12) ) \\ \\ (d^(2) y)/(dx ^(2) ) = - 11( - 12{x}^( - 13) ) \\ \\ (d^(2) y)/(dx ^(2) ) = 132{x}^( - 13) \\ \\ \huge \red{ \boxed{(d^(2) y)/(dx ^(2) ) = \frac{132}{ {x}^(13) } }}

User Ocramot
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.